The Highway Razdrto-Divača-Sežana and its Influence upon the Groundwater on Kras (Karst) - Novak, Dušan (Geologija, 1992)
The future highway Razdrto-Divača-Sežana will cross the area of intense karstification and the narrow district of the underground course of the Notranjska Reka. The karstic groundwater flows from various directions towards the Timava near Nabrežina and towards the pumping station of the Kras Water Supply System at Brestovica. The influences from the highway area can reach the Timava springs within 11 days. The adequate protection has to be forseen in order to prevent the pollution of the karst underground waters.